ERODIBILITAS TANAH PADA KAWASAN HUTAN LINDUNG GUNUNG MASARANG - Ayu Natia H. Djufri; Johan A. Rombang; Johny S. Tasirin (Universitas Sam Ratulangi, 2021)
Abstract This research aims to assess the value of soil erodibility in the Mount Masarang Protected Forest area Rurukan Village, Tomohon City. The research was conducted on 3 types of land cover, namely grasses/reeds land, agricultural land and secondary forests. For each type of land cover, 3 soil samples were taken. Soil sample points were determined purposively, the soil structure was observed and the soil permeability was measured using a permeameter with the constant water level method (Constant Head). Soil samples were analyzed in the laboratory to obtain data on soil texture and soil organic matter content, then K value was calculated according to the USLE method. The results showed that the highest soil erodibility was on agricultural land at 0.37 ton.jam.ft-tonf-1 .in-1 which is classified as a rather high class, while the lowest was on grass/reed land of 0.19 ton.jam.ft-tonf-1 .in-1 belongs to the low erodibility class. Factors causing high soil erodibility on agricultural land were a low clay content, higher silt and lower organic matter so that the soil is more easily eroded.Keywords: soil erodibility, protected forest, Mount Masarang.